The Plants Extract Toxicity Againts Achatina fulica (Ferussac, 1821) in Nyawai Ficus variegata (Blume) - Fajar, Fajar Lestari; Beny, Beny Rahmanto (Jurnal Wasian, 2020)
One of the problems in developing Nyawai plants is the attack of snail pests Achatina fulica (Ferussac, 1821) at seedling level of the plants. Plant damage caused by these pests is quite large and causes seedling death. One of the control efforts that can be done is utilizing biomaterials which have molluscicidal properties (can kill mollusks). This study aimed to determine the toxicity of some extracts of biomaterial to control Achatina fulica (Ferussac, 1821) pests. The research was conducted on a laboratory scale. The study used a factorial random design with 3 replications. The treatment consisted of four biomaterials namely sembung (Blumea balsamifera), gadung (Discorea hispida), tuba (Derris eliptica and betel nut (Areca catechu) with each concentration of 10.25.50 g/l. Each concentration used 4 snails as a test sample. The parameters observed were snail mortality, and Lethal Concentration (LC50 and LC95). The results showed that the gadung tuber extract had the highest toxicity as indicated by mortality of 75 % and the lowest LC95 value of 80.63 g/l. While the lowest toxicity is betel nut with mortality of 49.75 % and the highest LC95 value is 567.75 g/l. The Toxicity of tuba, pinang, and sembung are highest on 50 g/l concentration, excepted the gadung extract. In gadung extract, the highest toxicity was obtained on 10 g/l concentration. However, the application was consideration to the attack intensity of Achatina fulica (Ferussac, 1821) because the toxicity effect of biomaterial pesticide was slower than chemical molluscicide.